Scrotal cystocele presenting with renal failure - Lal, Vikash; Dhande, Ashish; Narayan, Pranav (International Journal of Research in Medical Sciences, 2017)
Extensive bladder herniation is rare. We hereby present a case of scrotal cystocele with chronic renal failure. It was managed successfully by initial nephrostomies and then definitive corrective surgery.